Togo: Thorny transitions and misguided aid at the roots of economic misery - Dirk Kohnert (Elections and democratization in West Africa 1990 – 2009, 2011)
The parliamentary elections of October 2007, the first free Togolese elections since decades, were meant to correct at least partially the rigged presidential elections of 2005. Western donors considered it as a litmus test of despotic African regimes' propensity to change towards democratization and economic prosperity. They took Togo as model to test their approach of political conditionality of aid, which had been emphasised also as corner stone of the joint EU-Africa strategy. Empirical findings on the linkage between democratization and economic performance are challenged in this paper because of its basic data deficiencies. It is open to question, whether Togo's expected economic consolidation and growth will be due to democratization of its institutions or to the improved external environment, notably the growing competition between global players for African natural resources. – – Résumé: Togo: transition épineux et l'aide erronée sont les racines de la misère économique: Les élections législatives d'Octobre 2007, les premières élections togolaises libres depuis des décennies, étaient destinées à corriger au moins partiellement les élections présidentielles truquées de 2005. Les donateurs occidentaux ont considérés ces élections comme un test décisif de la propension des régimes africains despotiques de changer vers la démocratisation et la prospérité économique. Ils ont pris Togo comme modèle pour tester leur approche de la conditionnalité politique de l'aide, et ont souligné que ce test soit une pierre angulaire de la stratégie conjointe UE-Afrique. Les résultats empiriques sur le lien entre la démocratisation et la performance économique sont contestées dans le présent document en raison de ses carences de base de données. Il est ouvert à la question, que la consolidation économique et la croissance prévus du Togo soient dus à la démocratisation de ses institutions ou de l'environnement externe améliorée, notamment la concurrence croissante entre les acteurs mondiaux pour les ressources naturelles africaines.
Additional information: Author's Version
Keywords: F35; F5; O55; O17; Z13; 330; Democratization; Fragile states; Togo; West Africa; Development Aid; Transition